2019
DOI: 10.31486/toj.18.0048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Infertility Among Patients With Isthmocele and Fertility Outcome After Isthmocele Surgical Treatment: A Retrospective Study

Abstract: Background: An isthmocele is a diverticulum on the anterior wall of the uterine isthmus at the site of a cesarean delivery scar. We evaluated the prevalence of infertility among patients with isthmocele, the resolution of symptoms, and infertility outcomes after hysteroscopic isthmoplasty. Methods: We conducted a retrospective study of 35 consecutive patients with symptomatic isthmocele between 2010 and 2015 at Hospital Piero Palagi in Florence, Italy. Patients with symptomatic isthmocele had postmenstrual abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
0
24
0
9
Order By: Relevance
“…Although the improvement rate was high, the calculated heterogeneity between the included studies was recorded to be significant (p-value: <0.001). However, the heterogeneity in Shi et al [34] and Calzolari et al [35] alone contributed to 50% of the overall estimated heterogeneity. This is because of the short period of follow-up, the nature of data selection, and the small sample size of included patients in those studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although the improvement rate was high, the calculated heterogeneity between the included studies was recorded to be significant (p-value: <0.001). However, the heterogeneity in Shi et al [34] and Calzolari et al [35] alone contributed to 50% of the overall estimated heterogeneity. This is because of the short period of follow-up, the nature of data selection, and the small sample size of included patients in those studies.…”
Section: Discussionmentioning
confidence: 94%
“…The overall pregnancy rate was found to be 69.77% with a significant heterogeneity (p-value=0.012) among the 11 studies that reported it at the end of the overall follow-up period [35,36,[38][39][40][41][42]. Along with the highest improvement rates, Tanimura et al [43] and Lei et al [44] also reported the highest pregnancy rates (100%) in women who underwent hysteroscopy as a surgical intervention for niches, while Xie et al [41] reported the lowest rates (25%).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the recent study by Lawrenz et al [7], an association between ICF and uncompromised clinical outcomes was mentioned, and the researchers conducted a detailed analysis of the possible factors of the production of effusion. Another study concluded that a subgroup of patients with symptomatic isthmocele may bene t from hysteroscopic isthmoplasty, which can help con rm the effect of ICF on pregnancy from another perspective [30].…”
Section: Main Ndingsmentioning
confidence: 99%
“…With the increasing CS rate worldwide, more infertile women are seeking to become pregnant with a scar on their uterus. Many studies have con rmed an uncompromised clinical outcome in patients with a history of CS and reported an even lower pregnancy rate when a niche was mentioned [7,24,30,32,33]. Previous studies agere that there is an impact in clinical outcomes, though some of them focus on isthmocele, and they describe blood or mucus on catheter [34].…”
Section: Implications Our Ndingsmentioning
confidence: 99%